PENERAPAN MODEL CPS (CREATIVE PROBLEM SOLVING) UNTUK MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA PADA PEMBELAJARAN PPKN KELAS X SMA NEGERI 1 GONDANGLEGI - Masruroh, Riris; Sri Untari; Arief Gunawan (Jurnal Tinta, 2023)
This study aims to examine the application of the Creative Problem Solving learning model to improve students' communication skills. This research was conducted in Class X - 3 PPKn learning at SMA Negeri 1 Gondanglegi. This study used a Classroom Action Research (CAR) design. Implementation of class action carried out with two cycles. The results showed that the application of the Creative Problem Solving learning model could improve students' communication skills. This is indicated by three aspects, namely the increase in teacher learning activities, student learning activities and student communication skills. The teacher's learning activity score in cycle I was 80, while student learning activities obtained an average score of 75 in cycle I, and the average student communication skill was 73 in cycle I. Cycle II showed an increase. The teacher's learning activity score became 87, while the average student learning activity scored 82, and the average student's communication skills increased to 82.